Extended effect after a single dose of type A botulinum toxin for asymmetric masseter muscle hypertrophy - Kasturi Bhattacharjee; Manpreet Singh; Harsha Bhattacharjee (Indian Journal of Plastic Surgery)
Facial asymmetry can either be physiological or pathological and is a common cosmetic concern. A 35-year-old Indian male presented with broad appearing lower face and prominent left jaw since adolescence. Parotid enlargement and other local disorders were ruled out. Ultrasonographic thickness of right masseter muscle was 13 mm while that of left was 14.9 mm, in unclenched state. Type-A botulinum toxin (T-ABT) was injected, evenly at five points, in both muscles within the “safe zone”. Using a 29 gauge needle, 15 and 25 international units were delivered to right and left masseters, respectively. Six months post — injection, a reduction of 2.9 mm and 4.4 mm was observed along with a reduced external facial asymmetry. At 24 months, patient maintains a satisfactory facial contour with no significant early or late post-injection complications. Intra-massteric injection of T-ABT can be used effectively as a primary or adjunct procedure for holistic oculo-facial sculpting.